Indonesian Local Community Livestock Deposit As A Step For Joint Benefits - Samas Adimisa Mishbah Habibie (IAIN Kendari, 2022)
This study aims to describe and discuss in writing about Cattle Deposits in the Style of the Indonesian Local Community in terms of profitability, risk and the social importance of humanity from the cattle production sharing system. At the same time, it provides knowledge to encourage the wider community to participate in investing (Desposito) their money in the form of cooperation for local livestock production. So later, it is expected to be a value for the common good and a driver of the quality of local livestock products. The method used is a literature review from a web browser and several research-related books. The main objects of this literature review research are local cattle farmers who use a profit-sharing system and cattle investors. The results of this study say that the profit sharing for local livestock, especially cattle, is very profitable for these livestock investors. The existence of capital also helps local farmers to buy cows to be raised. This collaboration will help local farmers earn income and benefit the community from livestock investment so that the common good is created.